Grammatical and lexical patterning of make in Asian learner writing: a corpus-based study of ICNALE - Lin, Ching-Hsi; Lin, Yen-Liang (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study investigates lexical and grammatical features of the high-frequency verb “make” in English written essays among Asian English as a foreign language (EFL) learners based on the ICNALE, the largest corpora focusing on various Asian learner groups. Examining how lexical and grammatical patterning of “make” differ between English native speakers (ENSs) and Asian learners from different countries, this study investigates overuse and misuse patterns of “make” and how they correlate to proficiency. Results show that all Asian learner groups shared similar tendency to use “make” substantially more than ENSs, with producing and causative uses most common and delexical use least common. However, Asian learners tend to produce fewer varieties of delexical uses compared with ENSs. The adjective and verb complements in the causative category by Asian learners also differ from that of ENSs. Rates and types of misuses by Taiwanese learners were independent of proficiency. It is also evident that the high-frequency verb “make” expresses a variety of meanings and there are differences in lexical as well as grammatical patterning between Taiwanese learners and ENSs. Pedagogical implications regarding the use of high-frequency verbs are included in the discussion.